Assessment of fungi and viruses in Artichoke (Cynara scolymus L.) in Da Lat, Lam Dong province - Tung, Hoang Thanh; Dac Khai, Hoang; Manh Cuong, Do; Van Thuc, Le; The Bien, Le; Viet Long, Ho; Tuyet Hanh, Vo Ha; Lan Anh, Hoang Le; Nhu Mai, Nguyen Thi; Minh Nguyet, Nguyen Nhu; Thi Hien, Vu; Quoc Luan, Vu; et al. (Vietnam Journal of Biotechnology, 2021)
Artichoke (Cynara scolymus L.), a high economic value crop, was brought to Vietnam by the French in the late 19th century. The artichoke was mainly planted in Lam Dong, Lao Cai, Vinh Phuc provinces, etc. At present, the disease situation of Artichoke plants and the lack of disease-free seedlings result in insufficient source of Artichoke for producers. Artichoke plants are mainly vegetative propagation and pathogens easily transferred from mother to daughter plants. Therefore, low propagation rate and fungal infection are two main factors hindering the expansion and development of Artichoke cultivation (in Lam Dong). Therefore, studying and evaluating the situation of fungi and viruses as well as establishing the in vitro propagation procedures in order to produce high number of disease-free seedlings are urgent for the current Artichoke shortage. In this study, samples of purple and white Artichoke varieties, which suspected fungal manifestations, were collected to assessment of fungi and viruses in artichoke. In addition, in vitro propagation by cultivating apical meristem was applied to produce disease-free seedlings. The recorded results showed that, 19 strains of mold were identified on purple and white Artichoke belonged to nine genera including Mucor (M. sp., M. circinelloides, M. fragilis, M. irregularis, and M. racemosus), Alternaria (Alternaria sp., A. alterinata, A. gaisen, A. tenuissima, and A. tillandsiae), Fusarium (F. acuminatum and F. solani), Cylindrobasidium (Cylindrobasidium sp1 and Cylindrobasidium sp2), Actinomucor elegans, Curvalaria clavata, Plectosphaerella oligotrophica, Phoma herbarum, Rhizomucor variabillis; meanwhile, the Tomato mosaic virus (ToMV) was isolated only purple Artichoke. Shoot explants obtained from apical meristem culture were completely disease-free and used for micropropagation at the next stage.